Diffusion-Weighted Imaging of the Macaque Brain Using Diffusion-Prepared Turbo Spin Echo in MRI - Jialu Zhang; Xiaotong Zhang (Applied Sciences, 2021)
Magnetic resonance imaging (MRI) integrates a static magnetic field, a time-varying gradient magnetic field at kHz and a radio-frequency (RF) magnetic field for non-invasive and real-time imaging; meanwhile, diffusion MRI (dMRI) pushes a further and closer dimension to the scale of neural fibers through sensitizing the gradient field to recognize water molecular displacement over distances of 1~20 μm along fibers. Contemporary dMRI approaches face challenges of magnetic field inhomogeneity as well as sequence-associated distortion and signal loss, the common remedies of which are repeated scans and post-reconstruction algorithms. In this study, over an anesthetized macaque with a customized head coil on 3 T MRI, we have proposed and implemented a monopolar diffusion-prepared module for turbo spin echo sequence (DP-TSE) as an alternative to achieve distortion-free, high-resolution diffusion imaging with improved SNR. The results showed high image quality and SNR efficiency as compared with conventional dMRI methods at millimeter level, allowing us to pursue submillimeter-scale dMRI over non-human primates (NHPs) in a relatively short scan time and without repetitions or post-processing, which could merit and advance our understanding of the structure and organizations of the primate’s brain.